Real-world treatment patterns and outcomes among patients initiating sequential regorafenib and trifluridine/tipiracil ± bevacizumab in patients with metastatic colorectal cancer in a US community setting (SEQRT2) - Bekaii-Saab, Tanios; Sruti, Ila; Shi, Junxin; Dai, Wei; Patton, Gregory; Appukkuttan, Sreevalsa; Hocum, Brian; Katta, Arvind; Babajanyan, Svetlana; Cosgrove, David (Frontiers in Oncology, 2025)
BackgroundRegorafenib and trifluridine/tipiracil (FTD/TPI) ± bevacizumab are both indicated for patients diagnosed with metastatic colorectal cancer (mCRC) in the third line or later. However, in the absence of recommendations regarding preferred treatment order, our study aimed to improve the understanding of real-world optimal treatment sequences.MethodsThis retrospective study assessed real-world outcomes and treatment patterns among mCRC patients who initiated sequential regorafenib and FTD/TPI ± bevacizumab between the first line and sixth line from September 2015 to November 2022 in The US Oncology Network. Patient and treatment characteristics were assessed descriptively overall and stratified by treatment order. The Kaplan–Meier methods were used for time-to-event endpoints, including real-world overall survival (rwOS), real-world progression-free survival (rwPFS), and real-world time to next treatment (rwTTNT) following sequence. Endpoints were also evaluated using Cox proportional hazards models.ResultsThis study examined 308 patients initiating sequential regorafenib and FTD/TPI, 156 patients initiating regorafenib first (R-T), and 152 patients initiating FTD/TPI first (T-R). Demographic and clinical characteristics were similar across cohorts. The population was predominantly male and had a mean age of 63 years and colon primary at diagnosis. The median rwOS was numerically longer among the R-T cohort compared to the T-R cohort (12.8 [11.2, 14.1] vs. 10.2 [8.8, 11.9] months). The median rwPFS was similar (3.4 [3.0, 3.6] vs. 3.4 [3.0, 3.7 months) for both the R-T and T-R cohorts. The median rwTTNT following sequence was numerically longer among the R-T cohort compared to the T-R cohort (9.3 [8.4, 10.3] vs. 8.6 [7.8, 9.4] months). Index treatment was not significantly associated with rwOS (Hazard Ratio (HR) = 1.2, p = 0.2), rwPFS (Hazard Ratio (HR) = 0.9, p = 0.4), or rwTTNT (Hazard Ratio (HR) = 1.1, p = 0.6).ConclusionTreatment sequence numerically favored R-T and provided an additional survival benefit of 2.6 months in this cohort, although this was not statistically significant. Providing access to regorafenib and FTD/TPI ± bevacizumab is critical to maximizing patient benefit and optimizing patient care in advanced stages of mCRC.